CXCL12 rs266085 and TNF-α rs1799724 polymorphisms and susceptibility to cervical cancer in a Chinese population - Yin, Geping (Int J Clin Exp Pathol, 2015)
Further research is required to identify single nucleotide polymorphisms (SNPs) associated with cervical cancer. The aim of this study was to assess the association of TNF-α/rs1799724 and CXCL12/rs266085 polymorphisms with susceptibility to cervical cancer in Han Chinese population in Shandong Province. 348 patients with cervical squamous cell carcinoma, including CIS (121) and invasive carcinoma (227), and 351 healthy controls. Genomic DNA was isolated from peripheral blood and genotyping for TNF-α/rs1799724 and CXCL12/rs266085 was carried out using TaqMan SNP Genotyping Assays. TNF-α/rs1799724 polymorphism showed the C-allele was less prevalent among cases as compared to controls (74.3% vs. 92.0%), while the T-allele was more prevalent among cases (P=0.000, OR=3.99, 95% C.I.: 2.90-5.51). CXCL12/rs266085 polymorphism showed the C-allele was less prevalent among cases as compared to controls (41.2% vs. 49.7%), while the T-allele was more prevalent among cases (P=0.001, OR=1.41, 95% C.I.: 1.14-1.74). The genotype and allele frequencies of these two SNPs did not differ between CIS and invasive squamous cell carcinoma (P>0.05). Moreover, the allele frequencies of rs1799724 were significantly different between controls without or with HPV infection (P<0.05). Neither the genotype nor allele frequencies of rs266085 were statistically different between HPV-negative and positive controls. TNF-α/rs1799724 and CXCL12/rs266085 polymorphisms are associated with cervical cancer. C->T polymorphism of these two SNPs and HPV infection are linked to high risk for cervical cancer.